Use of Suture Tapes Versus Conventional Sutures for Arthroscopic Rotator Cuff Repairs: A Systematic Review and Meta-analysis. Issue 1 (January 2022) - Boksh, Khalis; Haque, Aziz; Sharma, Ashwini; Divall, Pip; Singh, Harvinder
Background: Various suture materials are available for arthroscopic rotator cuff repair. More recently, suture tapes have become popular as they are perceived to be easier to use with less soft tissue irritation. However, little is known about their biomechanical and clinical properties compared with conventional sutures in rotator cuff repairs. Purpose: To perform a systematic review and meta-analysis on whether suture tapes are biomechanically superior to conventional sutures in arthroscopic rotator cuff repairs and whether this translates to superior functional outcomes and a lower incidence of retears. Study Design: Meta-analysis. Methods: The Cochrane Controlled Register of Trials, PubMed, Medline, and Embase were used to perform a systematic review and meta-analysis using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) criteria with the following search terms: (rotator cuff repair OR arthroscopic rotator cuff repair) AND ("tape" OR "wire" OR "cord" OR "suture"). Data pertaining to certain biomechanical properties (contact area, contact pressure, gap formation, load to failure, and stiffness), retears, and patient-reported outcome measures (PROMs) were extracted. The pooled outcome data were analyzed by random- and fixed-effects models. Results: After abstract and full-text screening, 7 biomechanical and 6 clinical studies were included. All biomechanical studies were on animals, with 91 suture tapes and 91 conventional sutures compared. Suture tapes had higher contact pressure (mean difference [MD], 0.04 MPa; 95% CI, 0.01-0.08; P = .02), higher load to failure (MD, 52.62 N; 95% CI, 27.34-77.90; P < .0001), greater stiffness (MD, 4.47 N/mm; 95% CI, 0.57-8.38; P = .02), and smaller gap formation (MD, −0.30 mm; 95% CI, −0.45 to −0.15; P < .0001) compared with conventional sutures. From the clinical analysis of the 681 rotator cuff repairs treated with a suture tape (n = 380) or conventional suture (n = 301), there were no differences in retear rates between the groups (16% vs 20% suture tape and wire, respectively; P = .26) at a mean of 11.2 months. Qualitatively, there were no differences in PROMs between the groups at a mean of 36.8 months. Conclusion: Although biomechanically superior, suture tapes showed similar retear rates and postoperative function to conventional sutures. However, higher-quality clinical studies are required to investigate whether there are no true differences.